Social Persuasion: A Strategy in Optimizing Students’ Self-Efficacy and Mathematics Performance - Abrenica, Emerlyn (RIRAI Publisher, 2025)
This study aimed to investigate the impact of social persuasion as a strategic intervention on Grade 7 students' self-efficacy and Mathematics performance. A pre-test- post-test experimental design was employed, with a self-efficacy questionnaire administered to assess students' perceived capabilities in solving mathematical problems. The social persuasion strategy was implemented over a period of 5 weeks, involving persuasive messages and feedback aimed at enhancing students' confidence and self-efficacy in Mathematics. After the implementation, results showed a significant positive relationship between self-efficacy and Mathematics performance, indicating that students' confidence in their abilities was strongly linked to their academic achievement. The post-test results revealed a significant increase in self-efficacy and Mathematics achievement compared to the pre-test scores, demonstrating the effectiveness of social persuasion in enhancing students' self-efficacy and Mathematics performance. The study concluded that social persuasion is a powerful strategic intervention in promoting students' self-efficacy and academic achievement in Mathematics. The findings suggest that incorporating social persuasion techniques in Mathematics instruction can foster a positive learning environment, boost students' confidence, and improve their academic achievement. The results have implications for teaching practices, highlighting the importance of promoting self-efficacy in students to enhance their academic success.